DEKONSTRUKSI TEORI USES AND GRATIFICATIONS DALAM ERA POST-TRUTH ANALISIS KRITIS TERHADAP KESADARAN PALSU PENGGUNA MEDIA SOSIAL DALAM PEMENUHAN KEPUASAN INFORMASI - Hasibuan, Imaida Noor; Mailin, Mailin; Rubino, Rubino (FIKRUNA: Jurnal Ilmiah Kependidikan dan Kemasyarakatan, 2025)
This research aims to deconstruct the theory of Uses and Gratifications in the context of the post-truth era, with an emphasis on a critical analysis of the misperception among social media users in meeting the needs of information. The post-truth era is characterized by the dominance of emotions and personal views that trump objective facts, which in turn affects the way individuals consume and process information. The conventional Uses and Gratifications theory views media users as active and rational individuals in choosing media to meet specific needs, such as entertainment, information, or social interaction. However, in the context of post-truth, this paradigm needs to be revisited. The study shows that social media users are often trapped in false consciousness due to social media algorithms and confirmation bias. The algorithm encourages the consumption of content that is in line with the user's personal beliefs, thus reinforcing the view without providing an opportunity for fact-verification. In addition, the phenomenon of echo chambers and filter bubbles further strengthens the isolation of information, which contributes to the formation of distorted reality. The approach used in this study is qualitative with critical analysis of relevant literature and case studies of social media users. The results of the analysis show that the information satisfaction felt by users is often illusory and does not reflect the fulfillment of real information needs. This false awareness creates the illusion of information fulfillment, even though the information consumed tends to be biased and incomplete. The conclusion of this study is that in the post-truth era, the theory of Uses and Gratifications needs to be reconstructed by considering the factors that affect false consciousness and information distortion. It is important for social media users to improve their media literacy and be critical of the sources of information they consume, in order to avoid the trap of false awareness and achieve more accurate and meaningful information fulfillment.